Cowden syndrome: Recognizing and managing a not‐so‐rare hereditary cancer syndrome. Issue 1 (11th August 2014) - Mester, Jessica; Eng, Charis
<x xml:space="preserve">Abstract</x> Cowden syndrome (CS) is an autosomal dominant hereditary cancer syndrome causing increased risk for breast, thyroid, renal, uterine, and other cancers as well as benign neoplasias and neurodevelopmental concerns. Timely diagnosis of affected patients is key, as early recognition allows for high‐risk screening and other preventative measures prior to a patient enduring multiple cancer diagnoses. This review will highlight the cardinal features of CS and management recommendations for affected patients. J. Surg. Oncol. 2015 111:125–130. © 2014 Wiley Periodicals, Inc.